Non-Binary Gender in Siyasah Syar'iyah Perspective: Study at Religious Universities in South Sulawesi - Arake, Lukman; Makkarateng, Ma'adul Yaqien; Abidin, Kurniati; Baharuddin, Elviana; Yusuf, Muhammad (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2023)
Non-binary gender is a legally recognized phenomenon that is present within global civilization, including the nation of Indonesia. The primary objective of this article is to analyze the concept of non-binary individuals within the context of religious universities, specifically from the standpoint of siyasah syar'iyah. This study employs a combination of qualitative and quantitative research methods, adopting a siyasah syar'iyah framework. Data was acquired utilizing two methods, including in-depth interviews, literature reviews, and surveys. The research study involved conducting interviews with informants who were specifically selected from the academic and religious communities in South Sulawesi. The literature under consideration comprises scholarly journal articles, books, and legal rules. Concurrently, a survey research study was undertaken at five Religious Universities located in the region of South Sulawesi. This study posits that under the framework of gender, non-binary is identified as a distinct category alongside men and women. Nevertheless, the Islamic law refutes the notion of gender and sexuality diversity, asserting that it contradicts sharia law, deviates from the inherent character of humanity, and raises legal issues such as inheritance and marriage. In addition to promoting non-discriminatory attitudes towards individuals, Islamic law also emphasizes the need of satisfying the rights of Non-Binary Gender individuals, provided that such fulfillment does not impede the realization of other human rights. According to siyasah syar'iyah, it is the responsibility of the state, as mandated by legislative rules, to ensure the provision of protection, guidance, and counseling to individuals, with the aim of fostering a life that promotes virtue and harmony within society.